Integrated study on the conservation of ecocultural heritage in the Tiantai Mountain area, China - Yanxuan Zhao; Hui Wu; Yingjia Fan; Hexian Jin; Yifan Wang; Lei Lu (Heritage Science, 2024)
Abstract This study deeply analyzes the ecocultural heritage of the Tiantai Mountain area in Eastern China, assesses its current status and explores effective mechanisms for its conservation and construction. Employing remote sensing technology, kernel density analysis and Minimum Cumulative Resistance Model, the study comprehensively evaluated the environmental characteristics of the region and its role in historical and modern conservation efforts. The results demonstrate the unique distribution patterns of ecocultural heritage in various conservation zones, such as restoration, controlled construction and core conservation zone. Furthermore, the study highlights the importance of religious beliefs and clan systems in the preservation of traditional knowledge and practices, with significant impacts of local community participation on conservation strategies. This research provides new theoretical and practical support for the implemention of ecocultural heritage conservation and development within religiously significant areas, highlights the need for conservation measures and synergistic strategies between ecological and cultural practices.